THU0592 Efficacy of Rehabilitation with TAI JI Quan on Disability, Quality of Life, Pain, Psychological Distress, Sleep in an Italian Cohort of Patients with Fibromyalgia Syndrome. (9th June 2015) - Del Rosso, A.; Paoletti, G.; Calà, M.; Maddali Bongi, S.
Abstract : Background: Fibromyalgia syndrome (FMS) is characterized by chronic widespread musculoskeletal pain, and muscle tenderness leading to disability, impaired quality of life (QoL), fatigue, and it is accompanied by sleep disorders and psychological distress. The Tai Ji Quan is a Chinese martial art that, integrating meditation, slow movements, deep breathing and relaxation, contributes to the distribution of Qi (vital breath) throughout the body. Some studies showed that Tai Ji Quan, in patients with rheumatic diseases and FMS, improved QoL, disability, and psychological distress (1-2). Objectives: To evaluate the efficacy of Tai Ji Quan on disability, QoL, fatigue, sleep and psychological distress in an Italian cohort of FMS patients. Methods: We enrolled 22 FMS patients (16 women and 6 men; age: 52, 24±12, 19 years; symptom onset: 8, 2±5, 39 years; diagnosis: 3, 25±2, 97 years). Eleven patients (Experimental Group) participated to a course of Tai Ji Quan Yang style of 17 lessons (1/week, 60 minutes each); 11 patients (Control Group) participated to an educational course about FMS (17 lessons; 1/week, 60 minutes each). At the enrollment (T0) and at the end of treatment (T1), all FMS patients were evaluated for disability, [Fibromyalgia Impact Questionnaire (FIQ) Health Assessment Questionnaire (HAQ)], QoL [Short-Form 36 (SF36)], fatigue [Functional Assessment of Chronic Illness-Fatigue (FACIT-F)], pain [Widespread Pain Index (WPI)], tenderness [Tender Points (TP)], Sleep Quality [Pittsburgh Sleep Quality Index (PSQI] and mood disorders [Hospital Anxiety and Depression Scale (HADS)]. Results: At T0, parameters of FMS patients were similar in the 2 groups. A T1 versus T0, patients of the Experimental Group improved significantly in FIQ (P=0.019), SF36 Summary Physical Index (P=0.016), WPI (P=0.037), tender points (P=0.0035), PSQI total (P=0.044) and PSQI sleep duration (P=0.025) HADS (total score: P=0.015; anxiety subscale: P=0.028) (Table ). Patients in the Control Group did not improve in any parameter. Conclusions: In our FMS patients, Tai Ji Quan improved disability, QoL, psychological distress, sleep quality and pain. So. it may be regarded as an effective rehabilitation method for treating FMS patients. However, our results should be confirmed by further long-term studies, with follow-up evaluations, in larger populations. References: Wang C.C, et al. Rheum Dis Clin North Am, 2011. Wang C.C, et al. N Engl J Med. 2010. Disclosure of Interest: None declared